SLR TENTANG INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN LITERASI SAINS PESERTA DIDIK - Dian Pratiwi; Rezky Awalia; Dewi Permata Ayu; Arifah Novia Arifin; Adnan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Numerous studies have demonstrated that students’ scientific literacy remains low, indicating the need for improvement in the learning process. Interactive learning that utilizes technology as a medium to enhance scientific literacy in the digital era is essential, considering the rapid advancement of technology and its inseparable role in everyday life. For science teachers and pre-service teachers, it is crucial to develop the competencies required to teach students in accordance with the demands of the times. This study employs a Systematic Literature Review (SLR) method aimed at comparing the findings of research articles published in Scopus-indexed journals. The keywords used to identify relevant articles in the Scopus database were “interactive learning” and “scientific literacy”, yielding 1,532 publications. After a process of screening and reduction based on inclusion and exclusion criteria (topic relevance, publication year, and article quality), 30 articles were selected for further analysis. The analysis revealed an increase in publications in 2025, with 18 articles published that year. The authorship analysis showed that research on interactive learning is predominantly conducted in Indonesia (60%), with additional contributions from Malaysia, South Korea, Australia, and the United States. The most prolific author identified was Putra. The findings indicate that technology integration is at the core of interactive learning development in the digital era, strongly supported by educational technology, artificial intelligence, and augmented reality. However, challenges remain in effectively integrating these technologies with pedagogical strategies to sustainably improve scientific literacy.